CoP nanoparticles encapsulated by graphitic layers and anchored to N-doped carbon nanoplates for enhanced bifunctional electrocatalytic properties for overall water splitting. (September 2019) - Li, Linghui; Song, Li; Xue, Hairong; Jiang, Cheng; Gao, Bin; Gong, Hao; Xia, Wei; Fan, Xiaoli; Guo, Hu; Wang, Tao; He, Jianping
Abstract: The design and fabrication of robust and inexpensive bifunctional catalysts for oxygen evolution reaction and hydrogen evolution reaction are very necessary for producing hydrogen by water electrolysis. Herein, we propose a bi-functional CoP@N-doped porous carbon nanoplate (CoP@NPCP) electrocatalyst, in which CoP nanoparticles with graphitized carbon capsule layers are uniformly anchored on the N-doped carbon nanoplates. Benefiting from structural advantages and componential superiorities, the CoP@NPCP exhibits remarkable electrocatalytic activity and superior durability for both oxygen evolution reaction and hydrogen evolution reaction in the alkaline medium. The present synthetic strategy is very feasible for the design of the metallic phosphide nanoparticles encapsulated in N-doped porous carbon nanoplates. Graphical abstract: The CoP@NPCP presents an excellent bifunctional electrocatalytic performance for HER and OER.Image 1